Analisis validitas dan praktikalitas modul fisika berbabis kemampuan berpikir kreatif pada pokok bahasan suhu, kalor dan teori kinetik gas untuk meningkatkan hasil belajar siswa kelas XI SMA/MA - Yulia Chairani; Hufri Hufri (Universitas Negeri Padang, 2020)
Based of Indonesian UNBK, 2019 West Sumatra province’s physics scores is 48.29, which is relatively low. And the analysis results of two high school physics textbooks in the city of Padang, using indicator of creative thinking ability assessment, is 46% (category : “less”). So, the two books do not support creative thinking abilities of students. One of the solutions is to make a physics module based on ability to think creatively. The purpose of this study is to determine the validity of the physics module based on the ability to think creatively, on the subject of temperature, heat and kinetic theory of class XI high school students. Conducted research was Research and Development (R&D) type. The validity test was conducted by 3 experts using a validation sheet containing an assessment of several components, feasibility of the content, the feasibility of construction, the component of inquiry, the feasibility of the language, the feasibility of the module display and the feasibility of creative thinking skills. Based on data analysis, the average validation value obtained was 86% with a very valid category. It can be concluded that the module based on the ability to think creatively is very valid for use in learning physics class XI high school.